A cascading approach to training discovery. Issue 1 (11th February 2019) - Galasso, Meg; Cohen, Rachael Anne; Thorpe Pusnik, Angie
Abstract : Purpose: The purpose of this paper is to illustrate why libraries should develop instructional plans to further integrate Web-scale discovery services into the academy, as well as propose a three-fold delivery plan to achieve this goal. Design/methodology/approach: This paper documents a strategy to integrate Web-scale discovery services into library training and instruction for multiple audiences. The strategy is informed by past analysis of discovery service search queries. Findings: It presents a three-part training plan that can be applied to multiple audiences, universities/colleges and even discovery service platforms. Practical implications: The strategies and practices detailed in this paper are easily adaptable to other institutions that currently subscribe to Web-scale discovery service products. Originality/value: This paper introduces an innovative approach toward transforming Web-scale discovery instruction across the academy, based on search query analysis.